Smart Lock using UTP Matric Card - EZANI, MOHD DANIAL SAUFI (IRC, 2020)
The workload and task needed by humans to carry out increase day-by-day. Having to worry about their task given to them, they have little to no time to worry about the safety and security of their personal belongings as well as their homes. Before technology became a necessity towards one’s life, it was time-consuming and burdensome to carry out everyday chores. Nowadays, technology has progressed rapidly and many types of technology have already been introduced. Internet-of-things or also known as IOT have been widely used by many developers and engineers to create their product either to be sold or to facilitate themselves in their daily tasks. Locks are used everywhere in the world for security in our daily life namely locking cars, locking a bicycle to the bicycle stand and door locks. Modern locks nowadays do not require any physical keys to lock and unlock them. Currently, locks for dormitories in Universiti Teknologi Petronas (UTP) are using the traditional locks for the doors. Keys are among the common thing to be misplaced or lost by humans. Having physical keys as dormitory keys in UTP could potentially let unauthorized people into the room as keys are easily duplicated in the nearest local hardware store. Another problem of having keys is that it is not convenient for students from all over the world to rush back to UTP just to retrieve their keys when they could have a day or two to spend with their families and friends. This Smart lock helps to reduce the keys being lost or misplaced as cards can be placed inside wallets and lanyards. Furthermore, this smart lock has a counter-measure if in case the students accidentally lost their cards or if the cards was duplicated by an unauthorized person. Since this lock is using the matric card of UTP students, this can remove the hassle of rushing back to UTP for the keys to the room.